Faktor Yang Mempengaruhi Penurunan Pelanggaran Lalu Lintas Di Kota Samarinda Tahun 2021 - Tasya Ananda; Muhammad Hairul Saleh (KIPS - Jurnal Kajian Islam Politik dan Sosial, 2025)
This study aims to understand and describe to the Factor Influencing the Decrease in Traffic Violations in Samarinda City In 2021. The results of this study indicate that there is a change in behavior that occurs in the people of Samarinda City in 2021 regarding Covid-19. Traffic violations in Samarinda City have decreased significantly due to the relationship between Covid-19 and the behavior of the people of Samarinda City tend to reduce the length of travel when leaving the house, changing modes or means of transportation because the people of Samarinda City are afraid and think that public transportation is the fastest medium for spreading Covid-19, increasing the speed of vehicles because when driving they are reluctant to linger on the highway, and being wiser in determining destinations and fears in traveling. Thus, the process of changing the behavior of the people of Samarinda City is determined by the conditions, namely Covid-19Application.